2D quantum turbulence in a polariton quantum fluid. (March 2020) - Koniakhin, S.V.; Bleu, O.; Malpuech, G.; Solnyshkov, D.D.
Highlights: Quantum turbulence might lead to self-organization. Energy is transferred from small to large scales. The inverse energy cascade is accompanied by the formation of fractal structures. Single vortices reduce the visibility of the energy cascade. Quantum fluids of light are favorable for the studies of quantum turbulence. Abstract: The coexistence of the energy and enstrophy cascades in 2D quantum turbulence is one of the important open questions in the studies of quantum fluids. Here, we show that polariton quantum fluids are particularly suitable for the possible observation of scaling on sufficiently large scales. The shape of raw energy spectra depends on the procedure of fluid excitation (stirring), but the energy spectra of clustered vortices always exhibit the -5/3 power law. In the optimal case, the cascade can be observed over almost 2 decades. The fractal nature of the structures is confirmed by the extracted fractal dimension.